Undoing Appropriateness: Raciolinguistic Ideologies and Language Diversity in Education - Flores, Nelson; Rosa, Jonathan (Harvard educational review, 2015)
In this article, Nelson Flores and Jonathan Rosa critique appropriateness-based approaches to language diversity in education. Those who subscribe to these approaches conceptualize standardized linguistic practices as an objective set of linguistic forms that are appropriate for an academic setting. In contrast, Flores and Rosa highlight the raciolinguistic ideologies through which racialized bodies come to be constructed as engaging in appropriately academic linguistic practices. Drawing on theories of language ideologies and racialization, they offer a perspective from which students classified as long-term English learners, heritage language learners, and Standard English learners can be understood to inhabit a shared racial positioning that frames their linguistic practices as deficient regardless of how closely they follow supposed rules of appropriateness. The authors illustrate how appropriateness-based approaches to language education are implicated in the reproduction of racial normativity by expecting language-minoritized students to model their linguistic practices after the white speaking subject despite the fact that the white listening subject continues to perceive their language use in racialized ways. They conclude with a call for reframing language diversity in education away from a discourse of appropriateness toward one that seeks to denaturalize standardized linguistic categories.